Hemispheric comparison of solar flare associated cosmic noise absorption (SCNA) from high latitude stations: Maitri (70.75°S, 11.75°E) and Abisko (68.4°N, 18.9°E) - Sinha, Shipra; Vichare, Geeta; Sinha, A. K. (Frontiers in Astronomy and Space Sciences, 2024)
The effects of solar flares in the D-region ionosphere at two high-latitude stations: Maitri (70.75°S, 11.75°E) and Abisko (68.4°N, 18.9°E), located in different hemispheres are studied. We analyzed 37 M-class flares and 6 X-class flares of the year 2014, which occurred when either or both stations were in the sun-lit side of the Earth. Cosmic Noise Absorption (CNA) curves are obtained using the datasets of riometers located at the two stations and are analyzed for all the 43 events under study. This paper discusses: (1) relationship between CNA and flare magnitude, (2) relationship between CNA and solar zenith angle (SZA), (3) hemispheric asymmetry in the observed solar flare associate CNA (or SCNA), and (4) the effect of background ionospheric condition in the SCNA magnitude at the two high latitude stations. It is observed that the solar flare effect in SCNA strongly depends on the SZA and flare intensity. Our analysis reveals that the flare response in SCNA for the year 2014 was stronger at Abisko than at Maitri. There is an observed hemispheric asymmetry in the solar flare ionization at D-region ionosphere for the given latitude. This asymmetry can be attributed to the previously enhanced background ionospheric ionization during particle precipitation processes. This study shows the need to establish an empirical relationship between the observed CNA vs flare intensity, SZA and latitudinal position; especially when we go higher in latitudes.